2019
DOI: 10.1016/j.eururo.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

RNA Splicing of the BHC80 Gene Contributes to Neuroendocrine Prostate Cancer Progression

Abstract: Background: Prostate adenocarcinoma (AdPC) progression to treatment-induced neuroendocrine prostate cancer (t-NEPC) is associated with poor patient survival. While AdPC and t-NEPC share similar genomes, they possess distinct transcriptomes, suggesting that RNA splicing and epigenetic mechanisms may regulate t-NEPC development. Objective: To characterize the role of alternative RNA splicing of the histone demethylase BHC80 during t-NEPC progression. Design, setting, and participants: The expression of BHC80 spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 29 publications
(48 reference statements)
0
28
0
Order By: Relevance
“…LnNE and DuNE cells were reported from our previous studies (31,32). All cell culture conditions have been previously reported (12,14). All lines used in this study tested negative for mycoplasma contamination and were authenticated by short tandem repeat assays.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…LnNE and DuNE cells were reported from our previous studies (31,32). All cell culture conditions have been previously reported (12,14). All lines used in this study tested negative for mycoplasma contamination and were authenticated by short tandem repeat assays.…”
Section: Methodsmentioning
confidence: 99%
“…The development of t-NEPC is regulated by PCa cell lineage plasticity, whereby prostate adenocarcinoma (AdPC) cells acquire a pluripotent stem-like phenotype followed by redifferentiation to NE lineage or undergo a transdifferentiation process to emerge as an NE lineage for t-NEPC tumorigenesis (5). These processes involve complex context-dependent mechanisms, including genomic alterations (7)(8)(9)(10), epigenetic reprogramming (11)(12)(13), alternative RNA splicing (12,14), and aberrant activation of transcriptional factors (7,(13)(14)(15). The diversity of genomic backgrounds and variability of molecular pathways help explain the heterogeneity of t-NEPC (16) and multiple driver genes discovered to date (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified 291 up-regulated and 498 down-regulated targets of PNO1 in PCa. Bioinformatics analysis showed PNO1 was involved in regulating multiple cancer related pathways, such as DNA repair [25], regulation of angiogenesis [26,27], translational initiation [28,29], RNA splicing [30,31], and cellular response to hypoxia [32,33]. Emerging studies showed these pathways played crucial roles in PCa progression and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…SRRM4 is a splicing factor specifically required for neural cell differentiation that was found to be elevated in NEPC (Zhang et al 2015) and, by careful analysis of whole-transcriptome sequencing data, implicated in the majority (>66%) of splicing alterations seen in this disease state (Li et al 2017). Key targets of SRRM4 include REST, a negative regulator of neurogenesis (Li et al 2017), as well Bif-1 (Gan et al 2018), MEAF6 (Lee et al 2017), and the histone demethylase BHC80 (Li et al 2019). The identities and roles of other splicing factors beyond SRRM4 that contribute to neuroendocrine lineage plasticity remain to be determined.…”
Section: Post-transcriptional Regulation Of Neuroendocrine Lineage Rementioning
confidence: 99%